Examining Mathematics Teachers' Views on 4MAT Teaching Model - erşen, zeynep bahar; güven, bülent (Advances in Social Sciences Research Journal, 2018)
4MAT teaching model has undoubtedly been mentioned and studied mostly in recent years. The aim of this study was to present the views on 4MAT teaching model of the elementary mathematic teachers applying the model. The case study was carried out with three elementary mathematics teachers having different occupational experience. Semi-structured interviews were used as data collection tools. Views of the teachers about 4MAT model application process were positive; teachers made different suggestions in order to apply model more efficiently and have the required success from these practices.